FUNCTIONAL DISABILITY INVENTORY AND ASSOCIATIONS WITH RACE, ETHNICITY, INCOME AND FOOD INSECURITY. (26th January 2023) - Zeky, Nicole; LeBlanc, Colleen; McDonough, Elizabeth; Moulton, Dedrick
Abstract: PURPOSE: Inflammatory bowel disease (IBD) is an autoimmune disease that consists of Crohn's Disease (CD) and ulcerative colitis (UC). Food insecurity is defined as limited or uncertain access to enough food. It is estimated that 1 in 7 children in the United States experience food insecurity or about 13 million children. Louisiana has one of the higher rates of food insecurity in the country with over 249, 000 children affected. Food insecurity has been associated with worse health outcomes in children including developmental risks, poor mental health, and poor educational outcomes. Functional Disability Inventory (FDI) is a measure of limitations in both physical and psychosocial functioning secondary to physical health. Our hypothesis is that patients in food insecure homes will have higher FDI scores compared to those in food secure homes. METHODS: This study is a prospective study of newly diagnosed IBD patients seen by the Division of Pediatric Gastroenterology at Children's Hospital of New Orleans. Patients were screened for food insecurity using the United States Department of Agriculture's food insecurity screening questionnaire and the American Academy of Pediatrics' Food Insecurity 2-Question Screen. Disability scores were obtained at diagnosis using the FDI self-reporting questionnaire if older than 12 years of age or a parent form was completed for patients less than 12. RESULTS: Our study consisted of 20 newly diagnosed pediatric IBD patients with an average age of 14.5 years. Nineteen (95%) patients had CD. Most patients were female (70%), non-Hispanic white (50%) with Medicaid (55%) as their primary insurance. Eight (40%) patients were African American and two (10%) were listed as other. Eight patients or their caregivers identified as living in a food insecure home (40%) and these patients averaged a FDI score of 10.2 The food secure group had an average FDI of 9.3. Non-Hispanic, white patients had an average FDI score of 10.5 while the minority patients had an average FDI of 8.5. Only two patients lived in an area with a median household income below poverty with an average FDI of 15.5. Ten patients lived below the state median income and had an average FDI was 8.2. Those patients living in areas above the state median income level, 8 total, had the highest FDI scores, 10.8. CONCLUSION: Food insecurity had higher rates of disability scores compared to families from food secure homes. Families in higher income areas and who were non-Hispanic white had higher FDI scores compared to minority patients and those in lower income areas. Further data will be collected with changes in FDI through the first 6 months of diagnosis. Additional larger studies are needed to determine a relationship between FDI scores and food insecurity in pediatric IBD.